Managing Conflicts and Maximizing Transparency in Industry-Funded Research. Issue 4 (17th August 2020) - Plottel, Gloria Stone; Adler, Rachel; Jenter, Chelsea; Block, Jason P.
Abstract: Background: Industry funding of research comes with important conflicts of interest, especially when research findings have financial implications for funders. When considering industry funding, academic investigators seek ways to mitigate and manage conflict to ensure integrity of research design, analysis, interpretation, and to protect researchers' and their institutions' credibility. This qualitative study's purpose was to conduct semi-structured interviews with expert stakeholders to gain insight into industry funding of research focused on nutrition and obesity, and determine the feasibility of developing a transparent process using an advisory board to help govern industry funding and manage conflict. Methods: We conducted seven semi-structured interviews with a purposive group of expert stakeholders representing varied perspectives. We distributed a summary of the advisory board concept to interviewees; developed and used a 16-question interview guide; and analyzed the interviews using open coding, manifest content analysis, axial coding, and code list reviews to identify and refine themes. Results: Most interviewees agreed that managing conflicts between industry funders and researchers was possible but difficult. They believed a carefully constructed advisory board empowered with specific responsibilities could help facilitate this process. They posited that strict guidelines are required to protect research quality and reporting, researcher(s)' and research institution(s)' reputations, and subsequent policy influenced by the research findings. They recommended specific guidelines and a framework for developing and administering the advisory board. Conclusions: A carefully constructed advisory board empowered with specific responsibilities could be useful to manage actual and perceived conflicts of interest, and increase transparency of research processes, funding, and results for industry-funded research. Stricter guidelines than those previously proposed in existing frameworks are needed to instill confidence in industry-funded nutrition and obesity research. A possible next step could include a pilot study of the advisory board concept to determine specific requirements for execution and to develop rigorous guidelines.